Investigation of the miR16-1 (C>T) + 7 Substitution in Seven Different Types of Cancer from Three Ethnic Groups. (26th October 2009) - Yazici, Hulya; Zipprich, Jennifer; Peng, Tao; Akisik, Elif Z.; Tigli, Hulya; Isin, Mustafa; Akisik, Ebru E.; Terry, Mary Beth; Senie, Ruby T.; Li, Lequn; Peng, Minhao; Liu, Zhiming; et al.
Abstract : Background . MicroRNAs are a type of small noncoding RNA molecules that have been shown to control gene expression in eukaryotes. Aberrant expression and alteration of miRNAs may be responsible for human diseases including cancer. An miR16-1 (C > T )  + 7 gene mutation has been previously found in familial chronic lymphocytic leukemia patients, one of which reported a family history of breast cancer. miR16-1 regulates the expression of bcl-2, which is important in retinoblastoma, and is located in a genomic region that is frequently lost in nasopharyngeal and hepatocellular carcinomas (HCCs). Therefore, miR16-1 may be potentially important in the etiology of several solid tumors. To understand the power of the miR16-1 (C > T )  + 7 mutation as a prognostic and diagnostic risk factor, we investigated the mutation in patients with seven different types of cancer including 188 with breast, 102 with ovarian, and 22 nasopharyngeal carcinomas, 96 HCC, 872 chronic myeloid leukemia (CML), 39 chronic lymphocytic leukemia (CLL), and 46 retinoblastoma cases from three different ethnic groups and of hereditary and sporadic etiology. Methods .5 ′ Nuclease TaqMan SNP genotyping assay was used to detect the miR16-1 geneC > T substitution. Results . The miR16-1 (C > T )  + 7 substitution was not detected in any of the groups studied. Conclusions . Considering the large scale of our study, the representation of different ethnicities and levels of hereditary risk, we conclude that the miR-16-1 (C > T )  + 7 mutation is not a good diagnostic or prognostic indicator of risk for the cancers tested.